EMBRIOGENESIS SOMATIK IN VITRO DAN REGENERASI PLANLET DARI TIGA VARIETAS ALFALFA (Medicago sativa L.) - Sulastri, Sulastri; Nawfetrias, Winda; Pinardi, Djatmiko; Rosdayanti, Henti (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
In Vitro Somatic Embryogenesis and Plantlet Regeneration of Three Varieties of Alfalfa (Medicago sativa L.)ABSTRACTAlfalfa (Medicago sativa L.) is a valuable plant as a source of food for animal, forage, pharmaceutical, medicine, food supplement, and human consumption.  In vitro selection technology combined with induction or spontaneous mutagenesis has been effective in altering or isolating genetic variability for desirable characters.  Consequently, a reproducible in vitro propagation technique of that plant is mandatory. The aim of the research was to obtain information on the embryogenic callus induction, somatic embryogenesis, and plantlet regeneration of three varieties of alfalfa. The results showed that an optimum embryogenic callus induction (82%) was obtained on Murashige & Skoog (MS) basal medium containing 2 ppm 2,4-dichlorophenoxyacetic acid (2,4-D), 2 ppm kinetin and 2 ppm a-naphthaleneacetic acid (NAA). Those embryogenic calli could subsequently develop into somatic embryos, which germinated and regenerated into normal plantlets on R1 medium consisting of MS nutrients without the addition of plant growth regulator.Keywords: alfalfa, callus, embryogenic, plantlets, regeneration ABSTRAKAlfalfa (Medicago sativa) adalah tanaman berharga sebagai sumber makanan untuk hewan, yaitu hijauan pakan ternak, farmasi, obat-obatan, suplemen makanan dan konsumsi manusia. Teknologi seleksi in vitro yang dikombinasikan dengan induksi atau mutagenesis spontan telah terbukti efektif dalam mengubah atau mengisolasi variabilitas genetik untuk karakter yang diinginkan. Oleh sebab itu, keberhasilan teknik perbanyakan in vitro yang telah terbukti dapat direproduksi dari tanaman tersebut menjadi syarat yang harus terpenuhi. Tujuan dari penelitian ini adalah untuk mendapatkan informasi mengenai induksi kalus embriogenik, embriogenesis somatik dan regenerasi planlet dari tiga varietas alfalfa. Hasil penelitian menunjukkan bahwa induksi kalus embriogenik optimal (82%) didapat pada media Murashige & Skoog (MS) dengan  2 ppm 2,4-dichlorophenoxyacetic acid (2,4-D), 2 ppm kinetin dan 2 ppm a-naphthaleneacetic acid (NAA). Kalus embriogenik tersebut dapat membentuk embrio somatik, embrionya berkecambah dan beregenerasi membentuk planlet normal pada perlakuan media R1 yaitu nutrisi MS tanpa penambahan zat pengatur tumbuh.Kata Kunci: alfalfa, embriogenik, kalus, planlet, regenerasi